Distribution. Subarctic in N Atlantic and Arctic oceans, from Davis Strait, Baffin I, and N Hudson Bay, to Newfoundland and Gulf of Saint Lawrence (Canada) and E to Greenland, Iceland, N Norway, White Sea, and Barents and Kara seas (N Russia). in Phocidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Subarctic in N Atlantic and Arctic oceans, from Davis Strait, Baffin I, and N Hudson Bay, to Newfoundland and Gulf of Saint Lawrence (Canada) and E to Greenland, Iceland, N Norway, White Sea, and Barents and Kara seas (N Russia). Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 180, DOI: 10.5281/zenodo.6607185